APRESIASI SENI TARI DI SMP NEGERI 5 PAYAKUMBUH (STUDI KASUS) - Gina Resti Febria; Idawati Syarif; Fuji Astuti (SENDRATASIK UNP, 2012)
Abstrak This research aims: (1) to describe Appreciation Dance at SMP Negeri 5 Payakumbuh. The issues raised in this research are the level of student’s appreciation in learning dance archipelago. (2) This research is a qualitative study using descriptive methods. Data was collected through literature study, observation, and interview. (3) The results of the research are to show that in learning of dance appreciation in SMP N 5 Payakumbuh found the rate of student’s appreciation to dance the dance Tortor archipelago has reached the expected level. The rate of student’s appreciation has been able to recognize, understand, appreciate and the student respect in learning the art of dance archipelago. The problem caused by the stimulation appreciative obtained by students, through methods and media appropriate for teachers in learning. In addition, the success in learning appreciation inseparable from the efforts of teachers to prepare themselves both in the planning, implementation and evaluation conducted by the teacher’s appreciation toward dance at SMP N 5 Payakumbuh.   Key Word: Apresiasi, Seni Tari, SMP Negeri 5 Payakumbuh